First Record of The Thecate Marine Dinoflagellate Protoperidinium abei (Peridiniales, Dinophyceae) in Indonesia - Danang Ambar Prabowo; Debora Christin Purbani; Diah Radini Noerdjito (Bogor Agricultural University, Indonesia, 2023)
Two identical dinoflagellate cell specimens were found in a seawater sample collected from Tanjung Pasir Beach (TPB; 6.01 S, 106.8 N), Banten, Indonesia and subjected to morphological characterization light microscopy (LM). The cells measured 71.97–72.86 µm long and 52.55–52.76 µm wide, fusiform or biconical-shaped, with tapered apical and antapical horns. A sharp and pointy spine was present at the antapex. The Kofoidean thecal plates arrangement pattern of the specimens was formulated as Po, 4', 2a, 7'', 3(?)c, 4s, 5''', 2''''. Based on this thecal plate tabulation formula combined with the cell morphologies, the specimens conformed to the original description of, and therefore identified as, Protoperidinium abei (Paulsen) Balech. This study constitutes the first record of P. abei in Indonesia and the first to illustrate and describe its detailed morphology using LM.